Trillions : thriving in the emerging information ecology - Lucas, Peter, 1952- (Wiley, 2012)
"The ultimate guide to prepare for--and prosper in--the next technology waveRevealing the fragility of current technology solutions--such as service-oriented architecture (SOA) and the Cloud--when confronted with the upcoming trillion-node information network, Trillions is an eye-opening book exploring what you need to do to meet the challenge of an information network comprising a trillion or more devices. Filled with diagrams and sidebars offering practical steps, visual case studies, and first person essays to drive home key points, this book exposes the limitations of current technology, inspiring you to meet the coming challenges resulting from the deployment of electronic devices and sensors that will surpass a trillion in number. Describes the upcoming Trillion Node network Explains how brittle our technology infrastructure is--and what we'll need to do to meet the challenge of a trillion or more nodes Offers diagrams, top ten lists, visual case studies, and first person essays Our relationship to information and complexity is evolving in an almost completely unrestrained way. Trillions shows how, done right, pervasive computing can make it possible for individuals and organizations to apprehend the world and its activities as a single system, not only making money for shareholders, but also fostering a more rational and humane world. This book is for anyone interested in helping build, and being part of, that world"--